THE IMPORTANCE OF ARTISTIC TRANSLATION IN THE DEVELOPMENT OF CULTURE, ART, LITERATURE, AND ORTHODOXY IN THE WORLD - Kurbanova, Muxabbat (Журнал иностранных языков и лингвистики, 2023)
Translation internationalism and the weapon of friendship between peoples. Through translation, national cultures enrich each other. Its unique influence can be felt everywhere in language, thought, culture, literary life, in art. The translation occupies a large place, especially in fiction with its vocabulary.